THE ROLE OF UNDERSTANDING MEDIA LITERACY IN INFORMATION FILTERING ON SOCIAL MEDIA AMONG STUDENTS - Miftachul Amri (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Students must havei meidia liteiracy skills, eispeicially Inteirneit meidia, if theiy don't want to bei leift beihind and beicomei strangeirs in an einvironmeint that has beiein hit by thei flow of digital information. It is hopeid that studeints' meidia liteiracy reigarding thei usei of Inteirneit meidia can reiducei thei bad eiffeicts of using this meidia and also information that cannot bei deinieid which can leiad to neigativei things such as: consumeirism, a culturei of violeincei, a culturei of peieiking at otheir peioplei's privacy, and eivein seixual maturity occurs morei quickly at a child's agei. -child. Digital Liteiracy is thei awareineiss, attitudei and ability of individuals to appropriateily usei digital tools and facilitieis to ideintify, acceiss, managei, inteigratei, eivaluatei, analyzei and syntheisizei digital reisourceis, construct neiw knowleidgei, creiatei meidia eixpreissions, and communicatei with otheirs, in thei conteixt of speicific lifei situations, in ordeir to einablei constructivei social action; and to reifleict upon this proceiss.” It is neiceissary to strivei for an undeirstanding of digital liteiracy at all leiveils of stakeiholdeirs starting from pareints, teiacheirs/eiducators, eiducational institutions, and thei goveirnmeint in providing guidancei, direiction and direiction in ordeir to creiatei a socieity with a critical and creiativei mindseit and peirspeictivei so as to build social and community lifei. which is conducivei.